The Influence of Product Variations, Korean Wave, and Electronic Word of Mouth On NCT's K-Pop Merchandise Purchase Decisions on Twitter Social Media In DKI Jakarta - Andriani, Adinda; Hardini, Resti; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to determine the influence of Product Variations, Korean Wave, and Electronic Word of Mouth on NCT's K-pop Merchandise Purchase Decisions on Twitter Social Media in DKI Jakarta. The sample in this study was 100 respondents, namely NCT fans who had made a purchase of NCT Merchandise on Twitter social media at least once. This study used quantitative methods using primary data. The data collection technique used was a questionnaire distributed to 100 respondents. In this study, researchers used inferential analysis techniques with multiple linear regression and used the Statistical Product and Service Solution (SPSS) program version 26.0. Based on the results of the research conducted, the results of multiple linear regression analysis, using a t-test where Product Variation (X1) has a positive and significant effect on Purchasing Decisions. Korean Wave (X2) has a positive and significant effect on Purchasing Decisions and Electronic Word of Mouth (X3) has a positive and significant effect on Purchasing Decisions. So it can be concluded that Product Variation, Korean Wave, and Electronic Word of Mouth have a positive and significant effect on Purchasing Decisions.